Cyber Deception Against Battery Drain DoS Attacks in Wireless Sensor Networks Using Signaling Game - Ines Carole Kombou Sihomnou; Abderrahim Benslimane; Ahmed H. Anwar; Gabriel Deugoue; Charles A. Kamhoua (IEEE Access)
Wireless sensor networks (WSNs) are essential in various domains such as environmental monitoring, industrial automation, healthcare, and military applications. Their ability to collect real-time data has transformed operations and decision-making. However, the limited energy resources of WSNs make them vulnerable to energy-draining attacks, particularly drain denial of service (DoS) attacks, which aim to exhaust their energy supply. To mitigate this issue, we propose a lightweight defense mechanism against energy-draining DoS attacks using signaling theory and game theory to model the interaction between an attacker and a regular node. In this model, the regular node sends signals to mask true information, deceiving the attacker. By applying a perfect Bayesian Nash equilibrium, we derive optimal strategies for both players, analyzing how deceptive signaling affects the attacker’s behavior and reduces their potential gain. This approach allows us to identify energy-efficient scenarios and improve network security by distorting the attacker’s perception of the target. Ultimately, a node with low energy capacity is able to protect its energy by emitting distorted signals.